A Mitochondrial Transcription Termination Factor, ZmSmk3, Is Required for nad1 Intron4 and nad4 Intron1 Splicing and Kernel Development in Maize. Issue 8 (1st August 2019) - Pan, Zhenyuan; Ren, Xuemei; Zhao, Hailiang; Liu, Lei; Tan, Zengdong; Qiu, Fazhan
Abstract: The expression systems of the mitochondrial genes are derived from their bacterial ancestors, but have evolved many new features in their eukaryotic hosts. Mitochondrial RNA splicing is a complex process regulated by families of nucleus-encoded RNA-binding proteins, few of which have been characterized in maize ( Zea mays L.). Here, we identified the Zea mays small kernel 3 ( Zmsmk3 ) candidate gene, which encodes a mitochondrial transcription termination factor (mTERF) containing two mTERF motifs, which is conserved in monocotyledon; and the target introns were also quite conserved during evolution between monocotyledons and dicotyledons. The mutations of Zmsmk3 led to arrested embryo and endosperm development, resulting in small kernels. A transcriptome of 12 days after pollination endosperm analysis revealed that the starch biosynthetic pathway and the zein gene family were down-regulated in the Zmsmk3 mutant kernels. ZmSMK3 is localized in mitochondria. The reduced expression of ZmSmk3 in the mutant resulted in the splicing deficiency of mitochondrial nad4 intron1 and nad1 intron4, causing a reduction in complex I assembly and activity, impairing mitochondria structure and activating the alternative respiratory pathway. So, the results suggest that ZmSMK3 is required for the splicing of nad4 intron 1 and nad1 intron 4, complex I assembly and kernel development in maize.